Composition and «pointless» painting in system of nonconventional approaches to creative process - V.H. Shcherbyna; L.F. Eyvas (Academy of Cognitive and Natural Sciences, 2022)
In article the points of view on «pointless» painting as on one of aspects of abstract art and nonconventional approaches to creative process are analysed.